Senataxin: genome guardian at the interface of transcription and neurodegeneration - Groh, M; Albulescu, L; Cristini, A; Gromak, N (Elsevier, 2016)
R-loops comprise an RNA/DNA hybrid and a displaced single-stranded DNA. They play crucial biological functions and are implicated in neurological diseases, including ataxias, amyotrophic lateral sclerosis, nucleotide expansion disorders (Friedreich ataxia and fragile X syndrome), and cancer. Currently, it is unclear which mechanisms cause R-loop structures to become pathogenic. The RNA/DNA helicase senataxin (SETX) is one of the best characterised R-loop-binding factors in vivo. Mutations in SETX are linked to two neurodegenerative disorders: ataxia with oculomotor apraxia type 2 (AOA2) and amyotrophic lateral sclerosis type 4 (ALS4). SETX is known to play a role in transcription, neurogenesis, and antiviral response. Here, we review the causes of R-loop dysregulation in neurodegenerative diseases and how these structures contribute to pathomechanisms. We will discuss the importance of SETX as a genome guardian in suppressing aberrant R-loop formation and analyse how SETX mutations can lead to neurodegeneration in AOA2/ALS4. Finally, we will discuss the implications for other R-loop-associated neurodegenerative diseases and point to future therapeutic approaches to treat these disorders.